La pandemia covid-19 en la educación en la Escuela de Educación Básica Abrahan paredes Gavidia del recinto Naranjapata, del cantón Caluma, provincia Bolívar en el año lectivo 2020 - 2021. - Andaluz Chango, María Bertila (2021)
The research carried out at the “Abrahan Paredes Gavidia” School of Basic Education determines that there are no students infected with the virus known as coronavirus that produces the COVID-19 disease; But by order of the Ministry of Education and the COE both at the national and cantonal level, the work in the classrooms with the students was suspended; who went on to receive classes virtually and through the washap, to comply with the projects developed by the Ministry in order to adapt the learning content to the reality of the moment. Faced with this reality and with the need to level the learning and knowledge acquired by the students, classroom work is planned, with the use of the efficient model, to seek better learning results; reason for which pedagogical methods and techniques are selected, which favor the participation of boys and girls, to improve their learning. Accordingly, the classes were planned for teaching, considering methods and techniques such as: problem solving method, problem-based learning, riddles; directed reading, self-regulated reading, commented reading and the summary, defining the processes to follow, so that the teacher guides the teaching process and the students achieve better learning. The class plans are in accordance with the requirements of the students and the proposals proposed by the Ministry of Education, thinking that better learning occurs in each student and therefore their school performance is optimal.